Developing Strategies for Improving The Performance of Educational Institutions Using The European Excellence Model: Pengembangan Strategi Peningkatan Kinerja Institusi Pendidikan Menggunakan European Excellence Model - Nurdiansyah, Rudi; Aufa, Muhammad Izzul; Sholikha, Nikmatus; Kuswardani, Chintia Dwi Wangsa; Widowati, Tamara Rahma (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
This study aims to develop performance improvement strategies for educational institutions based on theEuropean Excellence Model (EEM). The research is conducted at an upper secondary-level educational institution in Malang City using a self-assessment method and a questionnaire constructed based on seven criteria and 32 subcriteria of the EEM. The analysis involves scoring and examining correlations between the Direction and Execution dimensions with the Results dimension, particularly stakeholder perceptions. The institution scores a total of 360 points, identifying several priority areas for improvement, such as organizational culture and performance transformation. The proposed strategies leverage significant internal strengths to address the identified weaknesses